FIRST-LINE IMMUNOCHEMOTHERAPY FOR FOLLICULAR LYMPHOMA PATIENTS- SINGLE CENTER EXPERIENCE - Trajkova, Sanja; Krstevska Balkanov, Svetlana; Pivkova Veljanovska, Aleksandra; Ridova, Nevenka; Stojanovska Jakimovska, Simona; Cvetanovski, Milce; Dukovski, Dushko; Cadievski, Lazar; Kocoski, Bozidar; Stojanovski, Zlate; Nikolovski, Andrej; Labacevski, Bojan; et al. (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Introduction :  First line therapy of  follicular lymphoma (FL) patients is based on anti CD20 immmunotherapy combined with chemotherapy with or without anthracycline. Data from studies  presented a superior progression-free survival advantage  in favor of Obinutuzumab (O) vs. Rituximab (R)-based immunochemotherapies as first-line therapy in FL patients. Nevertheless the studies presented more adverse events at the same treatment group. Aim of the study : Evaluation of response from first line therapy  and adverse events of first-line rituximab vs. obinutuzumab-based immunochemotherapies. Materials and methods: This is a single center retrospective study presented with  143 adult FL patients  diagnosed ad treted at University clinic for hematology, Skopje, N.Macedonia in a period of five years (2018-2022). The response from first line therapy  and adverse events profile of first-line rituximab vs. obinutuzumab-based immunochemotherapies were compared.   Results:  A total of 143 patients were included in the analysis, 44% were treated with rituximab and 54,5% with obinutuzumab-based immunochemotherapy.Most of the patients 41,9% have advanced disease (Stage 4), FLIPI 3 (38,4%) and FLIPI 2 and 4 (21,6%). Most of the patiens had ECOG 1 (41%). Overall 33.5% of patients  experienced infections and 39,1% had COVID infection. Patients treated with O v.s  R have high rate of infection (44,8% and 13,3%) (p=0,005),  febrile neutropenia was found at 46,1% (O) and 34% (R) treated with G-CSF. At the end of the study complete response was achieved at 69,2%, partal response at 4,1%, 20% of patients died and 11% died from COVID infection  (25% of patients previously treated with R and 75% with O (p=0,001)). Conclusion:   In this  retrospective study of first-line treated FL patients comparing R- to O-based therapy, we did observe difference in adverese events profile in two treatment groups in favor of O treatment group. Keywords:   FL, Obinutuzumab; Rituximab, adverese events, infection.